Acute-on-chronic liver failure in a multi-ethnic Asian city: A comparison of patients identified by Asia-Pacific Association for the Study of the Liver and European Association for the Study of the Liver definitions - Rajoo, AS (Baishideng Publishing Group Inc., 2021)
10.4254/wjh.v9.i28.1133